Analisis Tingkat Stress, Cemas, Dan Depresi Pada Atlet Petanque Provinsi Gorontalo Saat Kompetisis - Dolin Rais; Edy Dharma Putra Duhe; I Kadek Suardika; Hartono Hadjarati; Suprianto Kadir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the levels of stress, anxiety, and depression among Petanque athletes of Gorontalo Province during competition. This research employed a quantitative descriptive method. The population of this study consisted of all Petanque athletes from Gorontalo Province, totaling 15 athletes, including 6 male athletes and 9 female athletes. The sampling technique used was total sampling, in which the entire population was selected as the research sample. The research instrument utilized was the Depression Anxiety Stress Scale (DASS-42) questionnaire developed by Lovibond & Lovibond to measure the athletes’ levels of stress, anxiety, and depression. Data analysis was conducted descriptively by calculating the percentage levels of each variable category. The results showed that the psychological conditions of Petanque athletes in Gorontalo Province during competition varied from normal to severe categories. Factors influencing these conditions included internal factors such as fear of failure, lack of self-confidence, and limited competition experience, as well as external factors such as pressure from coaches, performance demands, and the competition atmosphere.